Efficacy and safety of local–regional therapy combined with chemotherapy, immune checkpoint inhibitors and lenvatinib as first-line treatment in advanced intrahepatic cholangiocarcinoma: a multicenter retrospective cohort study - Shuofeng Li; Guanhua Yu; Mingming Wang; Shi Feng; Shanshan Wang; Mingjian Piao; Chengjie Li; Zixiang Zhou; Ziyu Xun; Boyu Sun; Jiongyuan Li; Nan Zhang; et al. (Cancer Immunology, Immunotherapy)
Abstract Background Local–regional therapy combined with immune checkpoint inhibitors (ICIs) and lenvatinib has shown promising anti-tumor activity in advanced biliary tract cancer. However, the efficacy and safety of integrating local–regional therapy with chemotherapy, ICIs, and lenvatinib in advanced intrahepatic cholangiocarcinoma (ICC) remain unclear. This study evaluated the efficacy and safety of first-line treatment combining local–regional therapy, chemotherapy, ICIs, and lenvatinib in advanced ICC. Methods This multicenter study included 47 advanced ICC patients receiving local–regional therapy (radiotherapy, hepatic arterial infusion chemotherapy, or transarterial chemoembolization) plus chemotherapy, ICIs, and lenvatinib from October 2019 to January 2025. Outcomes included overall survival (OS), progression-free survival (PFS), objective response rate (ORR), disease control rate (DCR), adverse events (AEs), and prognostic factors analysis. Results The multimodal therapy demonstrated mPFS of 10.2 months and mOS of 20.2 months. ORR and DCR reached 61.7% and 93.6%, respectively. Conversion surgery was performed in 10.6% (5/47) of patients, with 60.0% (3/5) achieving sustained remission. All patients experienced AEs, with grade 3–4 AEs in 66.0%, primarily including myelosuppression (23.4%), AST or ALT increased (19.1%), fatigue (14.9%), and pain (10.6%). No grade 5 AEs were observed, and all toxicities were manageable. Survival outcomes, tumor response rates, and grade 3–4 AE incidence showed no significant differences among local–regional therapy subgroups. Multivariate analyses identified impaired performance status as an independent predictor of poorer OS. Conclusions The combined regimen of local–regional therapy, chemotherapy, ICIs, and lenvatinib exhibited marked efficacy and a tolerable safety profile, establishing it as a viable first-line approach for advanced ICC.